TUGAS DAN PERAN HAKIM DALAM MELAKUKAN PENEMUAN HUKUM/RECHTVINDING (i.c Penafsiran Konstitusi sebagai Metode Penemuan Hukum) - Sudaryanto, Agus (Jurnal Konstitusi, 2012)
In order to renew law, judges are not merely to be trumpets of laws, but also to make laws through law discovery (rechtsvinding), although they are limited by accountable methods viewed from law science. This makes judges serve as law enforcers and also law reformers. Therefore, judges should make use of all their abilities to discover laws, by making interpretations (including constitutional intepretation), commonly employed such as grammatical, teleological or sociological, systematical or logical, historical, comparative and futuristic interpretations. Besides the law interpretation method, constitutional interpretation method may also be employed, such as textual, original, doctrinal, prudential, structural and ethical interpretation methods